PENGGUNAAN MEDIA VIDEO DAN MODEL MELALUI DISKUSI KELOMPOK UNTUK MENINGKATKAN HASIL BELAJAR ORGAN PENCERNAAN MANUSIA SISWA KELAS V MIN 2 LUMAJANG - ARIS RAHMAWATI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
Class situation in learning science, the situation is not the same as learning other knowledge. In learning science students must be active in the learning process. The reality in the field is that the teacher's role is still very dominant, students are seen as objects only. Even though this is not necessarily wrong, the reality in the field is that there are still many students who have difficulty in learning science. The problem needs to be found a way out, for that it is necessary to apply alternative learning models that can activate students, are fun and more meaningful. If students learn happily, it is expected that student learning outcomes will increase. One of the learning models that can activate and delight students is optimizing the use of video media and models through group discussions. The purpose of this study was to determine whether or not there was an increase in learning outcomes of the Human Digestive Organ. The success indicator is determined that at least 85% of students get a minimum score of 65. Group activity scores obtained from cycle to cycle always increase. On the other hand the score of teacher activity in the learning process the score obtained is at least 75%. The results showed that the mean, the initial test results were 59.46, the first cycle was 65.75 and the final average of the second cycle was 69.28. Meanwhile, students who finished studying in the initial test scored 46.43%, the first cycle was 71.42% and the second cycle was 85.71%. The average score of teacher activity in learning, the first cycle is 82.5% and the second cycle average is 86.25%. ABSTRAKSituasi kelas dalam belajar IPA, situasinya tidak sama dengan belajar pengetahuan lainnya. Dalam belajar IPA siswa harus aktif dalam proses pembelajaran. Kenyataan di lapangan peran guru masih sangat dominan, siswa dipandang sebagai objek saja. Miskipun hal ini belum tentu salah, namun kenyataan di lapangan masih banyak siswa yang kesulitan dalam belajar IPA. Masalah tersebut perlu dicari jalan keluarnya, untuk itu perlu menerapkan model pembelajaran alternatif yang bisa mengaktifkan siswa, menyenangkan dan lebih bermakna. Apabila siswa belajar dengan senang diharapkan hasil belajar siswa meningkat. Salah satu model pembelajaran yang bisa mengaktifkan dan menyenangkan siswa adalah mengoptimalkan penggunaan media video dan model melalui diskusi kelompok. Tujuan penelitian ini adalah untuk mengetahui ada atau tidak adanya peningkatan hasil belajar Organ Pencernaan Manusia. Indikator keberhasilan itu ditentukan sekurang-kurangnya 85 % siswa mendapat nilai minimal 65. Aktivitas kelompok skor yang didapat dari siklus ke siklus selalu naik. Disisi lain skor aktivitas guru dalam proses pembelajaran skor yang diperoleh minimal 75 %. Hasil penelitian menunjukkan bahwa rerata, hasil tes awal sebesar 59,46, siklus I sebesar 65,75 dan rerata akhir siklus II sebesar 69,28. Sedangkan siswa yang tuntas belajar pada tes awal skor yang dicapai 46,43%, siklus I sebesar 71,42% dan siklus II sebesar 85,71%. Rerata Skor aktivitas guru dalam pembelajaran, siklus I sebesar 82,5% dan rerata siklus II sebesar 86,25%.